Analysis of the Potential of Platelet Indices as a Predictor of Hematological Comorbidity in Patients with Diabetes Mellitus - Umar, Ani; Wenty, Darmayanita; Firdayanti; Susanti; Umar, Heni (YCAB Publisher, 2025)
Background: Diabetes Mellitus (DM) is one of the chronic diseases that is a global burden. The increase in DM cases poses a risk of complex comorbidities such as cardiovascular disease, kidney disease and hematological disorders. The Platelet indices (MPV, PDW, PCT, P-LCR) reflects platelet activation and has the potential to be a biomarker for predicting comorbidities, so it can help improve the quality of clinical management in DM patients. Objective: This study aims to evaluate the predictive potential of platelet indices as a biomarker of comorbidity hematology in DM patients. Methods: An analytical study with a cross-sectional design was conducted from June to July 2025 at the Bahteramas Regional Hospital, Indonesia, involving 100 patients with diabetes mellitus and 100 healthy individuals as controls selected through purposive sampling. Venous blood samples were taken from all participants to measure platelet indices (PLT, MPV, PDW, P-LCR) using an automated hematology analysis tool. Data analysis was carried out by an independent sample t-test to compare index values between groups, as well as an ROC curve to evaluate its predictive value against DM status, Statistical significance was set at p < 0.05. Results: showed that the mean platelet indices in the group of healthy individuals with PLT was 229.98 ×10³/μL and in DM patients with a mean value of 260.71 ×10³/μL, MPV in healthy individuals with MPV was obtained at 10.24 fL. In DM it rises to 10.46 fL. The PDW value in healthy individuals was 9.82 fL. In DM the average value increased to 11.80 fL, in Healthy Individuals PCT averaged 24.7%, In DM the value increased to 28.7%. The P-LCR value in healthy individuals was 22.12%. In DM, the average value increased to 25.80%, with a significant value of P< 0.05 which shows that between healthy patients and DM patients there is a significant difference in terms of PLT, MPV, PDW, PCT and P-LCR parameters. The ROC curve of each platelet parameter (PLT, MPV, PDW, PCT, and P-LCR) illustrates the sensitivity and specificity of the model in predicting the occurrence of comorbidities. This can be obtained from the Under the Curve Area Value (AUC) which shows that PDW has the highest AUC of 83.4%, which indicates the ability of the most effective parameters in predicting comorbidities in DM patients. Conclusions: This study shows that platelet indices, especially PDW values, has the most effective potential as a practical and easily accessible hematological biomarker for predicting comorbidity risk in patients with diabetes mellitus. These results confirm the role of the predictive value of platelet indices in early detection and risk stratification, which can support more proactive clinical decision-making and management of DM patients.